Results on Approximation Properties in Intuitionistic Fuzzy Normed Linear Spaces - Debnath, Pradip; Konwar, Nabanita (Theory and applications of mathematics & computer science, 2016)
In this paper we introduce the notions approximation properties (APs) and bounded approximation properties (BAPs) in the setting of intuitionistic fuzzy normed linear spaces (IFNLSs). Further, we define strong intuitionistic fuzzy continuous and strong intuitionistic fuzzy bounded operators and using them we prove the existence of an IFNLS which does not have the approximation property. In addition, we give example of an IFNLS with the AP which fails to have the BAP.